ASCERTAINMENT OF ELECTRIC-SUPPLY SCHEMES RELIABILITY FOR THE ATOMIC POWER PLANT AUXILIARIES - A. L. Starzhinskij (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The paper completes ascertainment of electrical-supply scheme reliability for the auxiliaries of a nuclear power plant. Thereat the author considers the system behavior during the block normal operation, carrying out current maintenance, and capital repairs in combination with initiating events. The initiating events for reactors include complete blackout, i.e. the loss of outside power supply (normal and reserve); emergency switching one of the working turbogenerators; momentary dumping the normal rating to the level of auxiliaries with seating the cutout valve of one turbo-generator. The combination of any initiating event with the repairing mode in case of one of the system elements failure should not lead to blackout occurrence of more than one system of the reliable power supply. This requirement rests content with the help of the reliable power supply system self-dependence (electrical and functional) and the emergency power-supply operational autonomy (diesel generator and accumulator batteries).The reliability indicators of the power supply system for the nuclear power plant auxiliaries are the conditional probabilities of conjoined blackout of one, two, and three sections of the reliable power supply conditional upon an initiating event emerging and the blackout of one, two, and three reliable power-supply sections under the normal operational mode. Furthermore, they also are the blackout periodicity of one and conjointly two, three, and four sections of normal operation under the block normal operational mode. It is established that the blackout of one bus section of normal operation and one section of reliable power-supply system of the auxiliaries that does not lead to complete blackout of the plant auxiliaries may occur once in three years. The probability of simultaneous power failure of two or three normal-operation sections and of two reliable power-supply sections during the power plant service life is unlikely.